The Evaluation of Entrance Surface Dose and Quality of Radiograph in Thorax Radiological Examination - Hermawan Dwi S (Journal of Global Pharma Technology, 2018)
Introduction: Computed Radiography (CR) is a technology of digitally medical imaging which is applied in x-ray generator. It is relatively easy to operate. Hence, the operators often use high parameter because they assume that it can ease image post-processing without considering radiation dose resulted by the process which is further received by patient’s organ penetrated by x-ray. It is mostly used on radiological examination of thorax at X-ray Department. Objective: This article aims to evaluate the relationship between ESD and the quality of resulted thorax radiograph as a protecting effort from radiation using ALARA principle. Method: The data were collected by taking pictures of Longman Phantom with kVp variations from 45 kVp to 105 kVp at 2 mAs to 32 mAs. TLD was utilized for the ESD measurement. Then, the radiographs were submitted to a radiologist to read and to convert them into diagnostic value. Result: This article results in several satisfactory imaging qualities based on the statistics of third quartile, that is on the radiation parameter of 75 kVp/16 mAs with dose value of 1.05 mSv, and of 85 kVp/8 mAs with dose value of 1.11 mSv, while BAPETEN allows parameter with dosage under 0.4 mSv on 55 kVp/8mAs, 65 kVp/4 mAs, 75 kVp/4 mAs , 85 kVp/2 mAs, and 105 kVp/2 mAs. Conclusion: The result of the research shows that setting the same value of kVp and increasing the value of mAs will increase ESD value.Keywords: kVp, mAs, ESD, Radiography of Thorax, Computed Radiography.